Управління ризиками в умовах зростаючої невизначеності - Kyfyak, Viktoria; Aleksandra, Zahul; Кашул, Олексій (Ефективна економіка, 2022)
Анотація. У статті обґрунтовано актуальність пошуку нових інструментів управління ризиками як необхідної умови здійснення успішної підприємницької діяльності. Визначено категорії «ризик» як ймовірність настання небажаної та непередбаченої події унаслідок прийняття управлінських рішень та дії факторів середовища господарювання та «управління ризиками» як систему методів та інструментів оцінки ризиків, їх аналізу та пошуку засобів їх уникнення або зменшення їх негативного впливу. Охарактеризовано функції та етапи управління ризиками в умовах невизначеності, описані новітні методи моніторингу ризику та зони ризику. Запропоновано для управління ризиками підприємницької діяльності використовувати цифрові інструменти виявлення та оцінки ризиків на основі когнітивних методів їх виявлення та комплексного підходу. Зроблено висновки, що імплементація ефективних інструментів управління ризиками у бізнес-процеси може стати каталізатором позитивних змін у стратегічному розвитку бізнесу.
Risk management in conditions of growing uncertainty
Summary. Fluctuations in economic systems, uncertainty and new social challenges are the conditions for the economic entities functioning, which form risk as an entrepreneurial activity sign. Risk management is a necessary function of entrepreneurship and a component of the business environment. In modern conditions, the research actuality and search for effective risk management mechanisms is obvious, because the enterprises strategic success depends on its ability to make management decisions and achieve goals by assessing risks. The aim of the study is the theoretical characteristics of the risk management process from the standpoint of a systems approach and the analysis of practical risk management tools under conditions of high uncertainty caused by coronary crisis. The article substantiates the relevance of finding new risk management tools as a necessary condition for successful business. The categories "risk" are defined as the probability of undesirable occurrence and unforeseen events due to management decisions and the action of environmental factors and "risk management" as a system of methods and tools for risk assessment, analysis and finding ways to avoid or reduce their negative impact. The functions and stages of risk management in uncertainty conditions, the main methods of risk monitoring and risk zones are described. The risks of entrepreneurial activity in the conditions of coronary crisis are analyzed and it is revealed that the main internal risks are slow reforms and growing state budget deficit, and external - the risks of a new global crisis and other waves of the pandemic in the world. The newest tools of risk management on the basis of cognitive methods of detection and the complex approach are offered. The approach to risk management in conditions of growing uncertainty involves changing the approach to risk management, which should be aimed at improving the sustainability of enterprise strategy, the tools formation to prepare for new crises, cover the entire system of risks from operational to strategic at all levels of business using modern risk management technologies. Keywords: risks, risk management, uncertainty, risk assessment, cognitive calculations.
Keywords: Ключові слова: ризики, управління ризиками, невизначеність, оцінка ризиків, когнітивні обчислення.